Gender differences in achievements among students of the Iraqi college of medicine (Baghdad Science Journal, 2004)
This study was conducted to test the hypothesis that the duration of time spent by the student inside the examination rooms answering the all kinds of written ex-amination questions has some kind of a positive effect on the final score he will get from that exam. And if there arc gender differences in this respect. Students and methods: Data on the final examinations of the autumn quarter was gathered on 892 examina-tions conducted at the end of this quarter , this included male participants of 566 and females of 326. Examinations were on twenty different subjects , including all of the first five years of the undergraduate students of Iraqi College of Medicine for the academic year 2002 — 2003 . The scheduled time of the examinations was 3 hours.A questionnaire for that purpose was constructed by the researchers and filled by the examination supervisors of the examination rooms . The scores we got from the offi-cial records of the examination committee of the college . Information gathered in-cluded year or stage of the student , subject of examination, gender, duration of time spent by every student inside the examination room and final score on that examina-tion. data were entered into a computer statistical program SPSS 7.5 and statistically analyzed. The results showed 1. The mean duration of stay of students in examination rooms was 125.01 SD=39.32 out of 180 minutes. 2. Females significantly spend more time in the examination rooms (p=0.008), but they do not achieve better marks for this. 3. No significant gender difference in mark acquisition although females regis-tered insignificantly better marks. 4. Mark is affected by the duration of time spent in examination rooms significant positive correlation (p=0.001). 5. However total duration of stay affected the final mark for males (p=0.01). but did not affect that of the females (p=0.27) 6. Females significantly spend more time in the examination rooms (p=0.008), but they do not achieve better marks for this. 7. Males benefit from time spent in getting significantly better results (p-0.01) 8. According to grades or year or stage of the student the longest time spent was significantly more in the first year (p=0.0001) but there was no correlation with the year . The highest marks were recorded by the first year students (p=0.0001)